Современные технологии производства компонентов моторных топлив: учебник для вузов - Солодова Н. Л. Наталия Львовна; Башкирцева Н. Ю. Наталья Юрьевна; Абдуллин А. Н. Аяз Илнурович; Теляшев Р. Г. Раушан Гумерович; Обрывалина А. Н. Анна Николаевна (Старый Оскол, ТНТ, 2018)
Авт. указ. на обороте тит. л.